Захист об'єктів критичної інфраструктури в умовах кібервійни - Дорофєєва, К. І. (ХНУРЕ, 2024)
The current issues of protecting critical infrastructure facilities in the context of cyber warfare is considered. In addition, the importance of continuously updating and improving protection measures to effectively counter rapidly changing cyber threats is considered. The threats that affect the security of critical infrastructure in the conditions of cyber warfare have been identified The importance of paying attention to this issue and emphasizing the need for continuous improvement of cybersecurity strategies to ensure the continuity of critical infrastructure in the era of digital threats is described.
Keywords: об'єкт критичної інфраструктури; кібервійна